Hovhannes Tumanyan in Edward Jrbashyan’s life - HOVHANNISYAN, SUSANNA (Bulletin of Yerevan University B: Philology, 2021)
Ed. Jrbashyan is an author of many valuable scientific publications on Tumanyan-study. He studied the Armenian poet’s works in all genres - poems, ballads, and prose. He broke untouchable vulgar sociological stereotype of analyzing Tumanyan’s works ruling more than 3 decades, and emphasizing the aesthetic side of his works. The primitive analysis of the writer’s works developed into a serious scientific speech; due to him Tumanyan-study entered a new stage of development, which can be called as Jrbashyan-style. Ed. Jrbashyan’s research played a decisive role in the further development of Tumanyan- study providing quite a new quality in that field. In addition to being a talented researcher Jrbashyan was also a wonderful organizer and leader in Armenian literary science. Today the academician’s works still have a guiding character. Edward Jrbashyan’s literary studies once again confirmed Tumanyan’s eternal existence in the culture of our nation as well as in the history of world literature.